Aspects of Movement Ecology and Habitat Use of Migratory Raptors Using Satellite Telemetry from India to Central Asia - Mohan Ram; Devesh Gadhavi; Aradhana Sahu; Nityanand Srivastava; Tahir Ali Rather; Vidhi Modi; Akshita Patel; Lahar Jhala; Yashpal Zala; Dushyantsinh Jhala (Birds)
Single individuals of the Greater Spotted Eagle (Clanga clanga), Indian Spotted Eagle (Clanga hastata), Tawny Eagle (Aquila rapax), Western Marsh Harrier (Circus aeruginosus), and two Pallid Harriers (Circus macrourus) were deployed with satellite transmitters in 2021 to study their home ranges, habitat associations, movement, and migration patterns. Data were collected for a combined number of 2291 days, providing 84,544 locations. Home ranges were calculated as kernel utilization distributions and expressed as 95% KDE and core areas as 50% KDE. Overall, eagles had larger home ranges (mean ± SD) of 942.70 ± 937.83 km2 compared to harriers, 43.84 ± 35.55 km2. Among eagles, the Greater Spotted Eagle had the largest home-range size of 2147.03 km2 calculated in Kazakhstan, while the female Pallid Harrier had the smallest home range of 5.74 km2 in Russia. Daily and monthly distances varied among eagles and harriers. The female Pallid Harrier covered the longest average monthly distance of 8585.43 ± 11,943.39 km, while the shortest monthly distance of 1338.22 ± 716.38 km was traveled by the Indian Spotted Eagle. All tagged birds migrated toward higher latitudes in the Northern hemisphere, except the Indian Spotted Eagle, which migrated to Pakistan. The male Western Marsh Harrier covered the longest migration distance in a shorter span of time, while the female Pallid Harrier took the longest to cover its migration distance. Overall, the daily distance covered during migration varied from 115.09 km traveled by the Indian Spotted Eagle to an overwhelming distance of 2035.85 km covered by the male Western Marsh Harrier. Scrubs, water bodies, croplands, and settlements were important habitat features associated with eagles, while croplands, open scrub, and built-up areas were associated with the female Pallid Harrier. The male Western Marsh Harrier was found to be primarily associated with saltpans and salt-affected areas having emergent vegetation. This study presents new insights into the movement and spatial ecology of long-distance migrant raptors that winter in Western India. We provide preliminary support for the use of the Western Circum–Himalayan Corridor as one of the important corridors of the Central Asian Flyway that warrants much appreciation among the current set of flyway corridors.